Depression mediates the association between insula‐frontal functional connectivity and social interaction anxiety. Issue 14 (21st May 2022) - Zhao, Weihua; Zhang, Xiaolu; Zhou, Xinqi; Song, Xinwei; Zhang, Zhao; Xu, Lei; Zhou, Feng; Kendrick, Keith M.
Abstract: High rates of comorbidity between depression and anxiety are frequently observed. However, few studies have investigated the relationship between depression and social interaction anxiety using a dimensional approach. The current study aimed to explore the associations between depression and social interaction anxiety with a multivariate approach in a comparably large dataset ( n  = 194, 95 males). All participants completed a structural and a resting‐state functional magnetic resonance imaging (fMRI) scan and self‐report measures of depression via Beck's Depression Inventory II and social interaction anxiety by social interaction anxiety scale. Voxel‐based morphometry (VBM) results first identified grey matter volumes of insula were positively correlated with depression dimension scores. Next, whole brain seed‐to‐voxel analyses were conducted using a VBM‐identified insula as a seed region to examine associations between depression/social anxiety and functional connectivity. The results suggested that a significant positive effect of depression/social anxiety was found on the connectivity between insula and dorsal lateral prefrontal cortex (dlPFC). Moreover, variations in depression meditated the association between insula‐dlPFC connectivity and social interaction anxiety. Overall, the results indicate that individual differences in depression relate more to insula‐dlPFC coupling compared to social interaction anxiety. Abstract : A positive correlation between depression scores and total grey matter volumes of insula. The insula‐dlPFC coupling was positively associated with both depression and social interaction anxiety scores. The insula‐dlPFC connectivity contributed more to depression dimensions than to social interaction anxiety.